H2-quartz and cushion gas-quartz intermolecular interactions: implications for hydrogen geo-storage in sandstone reservoirs - Sikiru S.; Al-Yaseri A.; Yekeen N.; Soleimani H.; N B.N.; Hamza M.F.; Ghotbi M.Y. (Springer, 2025)
Emissions of carbon dioxide (CO2) from fossil fuel usage continue to be an incredibly challenging problem to the attainment of CO2 free global economy; carbon Capture and Storage (CCS) and the substitution of fossil fuel with clean hydrogen have been identified as significant primary techniques of achieving net zero carbon emissions. However, predicting the number of gases trapped in the geological storage media effectively and safely is essential in attaining decarbonization objectives and the hydrogen economy. Successful underground storage of carbon dioxide and hydrogen depends on the wettability of the storage/cap rocks as well as the interfacial interaction between subsurface rocks, the injected gas, and the formation of brine. A key challenge in determining these factors through experimental studies is the presence of conflicting contact angle data and the difficulty of accurately replicating subsurface conditions in the laboratory. To address this issue, molecular dynamics simulations offer a microscopic approach to recreating subsurface conditions and resolving experimentally inconsistent results. Herein, we report the molecular dynamics simulation results for hydrogen (H2) and cushion gas (e.g., CO2 and N2) on quartz surfaces to understand the capillary and trapping of these gases in sandstone formations. The results of these three gasses were compared to one another. The simulation predictions showed that the intermolecular interactions at the CO2-quartz surface area are more substantial than at the N2 and H2-quartz interface, suggesting that the quartz surface is more CO2-wet than N2 and H2-wet under the same circumstances. In addition, it was found that CO2 has a substantially higher adsorption rate (? 65 Kcal/mol) than N2 (? 5 Kcal/mol) and H2 (? 0.5 Kcal/mol). This phenomenon can be explained by the fact that CO2 density is substantially larger than N2/H2 density at the same geo-storage conditions. As a result, CO2 could be the most favorable cushion gas during underground hydrogen storage (UHS) because a higher CO2 residual is expected compared to H2. However, due to the Van der Waal Interaction force with quartz, only a small amount of H2 can be withdrawn. ? The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.